Evaluasi Usability LMS ELENA Menggunakan Metode System Usability Scale dan Heuristic Evaluation di STT Nurul Fikri - Erlangga Rahimi; Hana Fauziah; Laisa Nurin Mentari (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2026)
As the primary platform for online learning at STT Terpadu Nurul Fikri, the ELENA LMS requires periodic evaluation to ensure that its interface quality and user interaction patterns remain optimal. Such evaluation is crucial for enabling students to participate actively in virtual classes. This study examines the relationships between system usability, user interaction quality, and student academic engagement. A quantitative approach employing descriptive and explanatory methods was used, involving 120 active students as respondents. Data were collected using the System usability scale (SUS) and Heuristic evaluation—alongside instrument validity and reliability testing—and subsequently analyzed using descriptive statistics and Spearman Rank correlation. The results show mean scores of 34.37 for usability, 34.06 for user interaction, and 34.89 for student engagement. The instruments proved valid, with Cronbach’s Alpha values of 0.616, 0.862, and 0.871, respectively. Correlation analysis revealed significant positive relationships between the variables, with the strongest link observed between user interaction and student engagement (r = 0.743; p < 0.001). These findings confirm that the ELENA LMS effectively supports the online learning process, although improvements to navigation, system feedback, and interface controls are still needed to enhance the user experience.Keywords: Heuristic evaluation; Learning management system; Usability; User interaction; System usability scaleAbstrakSebagai sarana utama pembelajaran daring di STT Terpadu Nurul Fikri, LMS ELENA perlu dievaluasi secara berkala untuk memastikan kualitas antarmuka dan pola interaksi penggunanya tetap optimal. Evaluasi ini penting agar mahasiswa dapat berpartisipasi aktif dalam kelas virtual. Penelitian ini menelaah keterkaitan antara aspek kegunaan sistem, kualitas interaksi pengguna, serta tingkat keterlibatan akademik mahasiswa. Pendekatan kuantitatif dengan metode deskriptif dan eksplanatori digunakan, melibatkan 120 mahasiswa aktif sebagai responden. Data dikumpulkan melalui System usability scale (SUS), Heuristic evaluation, serta uji validitas dan reliabilitas instrumen, kemudian dianalisis dengan statistik deskriptif dan korelasi Spearman Rank. Hasil menunjukkan rata-rata skor usability 34,37, user interaction 34,06, dan student engagement 34,89. Instrumen terbukti valid dengan nilai Cronbach’s Alpha masing-masing 0,616, 0,862, dan 0,871. Analisis korelasi memperlihatkan hubungan positif signifikan antarvariabel, dengan keterkaitan paling kuat antara interaksi pengguna dan keterlibatan mahasiswa (r = 0,743; p < 0,001). Temuan ini menegaskan bahwa LMS ELENA telah mendukung proses pembelajaran daring secara efektif, meskipun perbaikan pada navigasi, umpan balik sistem, dan kontrol antarmuka masih diperlukan untuk meningkatkan pengalaman pengguna.